2019
DOI: 10.24251/hicss.2019.056
|View full text |Cite
|
Sign up to set email alerts
|

Developing a User Typology for the Analysis of Participation in Enterprise Collaboration Systems

Abstract: In this paper, we propose a user typology for Enterprise Collaboration Systems (ECS). We draw on and extend findings from previous research in the area of CSCW and Social Collaboration Analytics. The proposed typology includes: (1) a definition of user types, (2) dimensions of ECS use and (3) a classification of action (event) types. The typology contains the following user types: creator, contributor, lurker, inactive and non-user. These types are characterized by differences in the following dimensions: type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The last three user types refer to employees who are not active at all on a platform because they did not use it for a long time, never logged in or never possessed login information. Schwade and Schubert (2019) also revealed that scholars focused on the role and characteristics of lurkers, while the discussion of other user types is limited. Furthermore, there is no consensus on the definition of the individual types.…”
Section: Background: Enterprise Social Media User Typologymentioning
confidence: 99%
See 1 more Smart Citation
“…The last three user types refer to employees who are not active at all on a platform because they did not use it for a long time, never logged in or never possessed login information. Schwade and Schubert (2019) also revealed that scholars focused on the role and characteristics of lurkers, while the discussion of other user types is limited. Furthermore, there is no consensus on the definition of the individual types.…”
Section: Background: Enterprise Social Media User Typologymentioning
confidence: 99%
“…In conclusion, studies analyzing the factors that distinguish the different types of ESM users are still fragmented and provide partially contrasting results. In addition, most of the proposed typologies are inconsistent because they mix different dimensions, such as type of use, frequency of use and variety of purposes for use (Schwade and Schubert, 2019). In light of this, we proposed a bi-dimensional classification of ESM users and apply it to analyzing the case company that adopted an ESM platform to support employees' KM activities.…”
Section: Background: Enterprise Social Media User Typologymentioning
confidence: 99%
“…The categories consumption, contribution and creation, for example, allow the identification of different users types e.g. creator, contributor, lurker, inactive and non-user [38].…”
Section: Structural Vs Transactional Viewmentioning
confidence: 99%
“…[22,41,75,76], and related user types (e.g. creator, contributor, lurker) [72] are measured. Muller et al [42] propose the return on contribution (ROC) construct, a ratio between production and consumption, and costs and benefits, respectively.…”
Section: Enterprise Collaboration Platform Outcomes and Benefits Resementioning
confidence: 99%